Physicochemical and sensory evaluation of reinforce bread with partial replacement of wheat flour (Triticum aestivum) by corn (Zea mays) and potato (Solanum tuberosum) flours - Obregón, Antonio (2013)
It was realized the sensorial evaluation and were studied the chemical composition and nutritional value of iron-fortified bread, with partial replacement of 10% of its wheat flour content by potato and corn flour, obtaining a bread with soft texture, palatable and very good acceptability for children of school age. The elaborated bread contains protein 13,10%; fat 9,80% and carbohydrates 50,32%, with an energy value of 341,88 kcal/100 g and an iron content 10,13 mg/100 g, that satisfies the recommended dietary allowance of iron for schoolchildren.